EXPLORING THE POTENTIAL OF BLENDED LEARNING AND LEARNING MANAGEMENT SYSTEMS (LMSS) FOR HIGHER EDUCATION IN ACEH - Zamzami Zainuddin (Englisia: Journal of Language, Education, and Humanities, 2015)
The paper aims to explore the potential of the blended learning approach for higher education in Aceh. This is a conceptual paper that attempts to provide the concepts and theories associated with implementing the blended learning approach on college-level students and lecturers. Blended Learning is a learning model that is enriched with traditional learning methods and online education materials. In a typical blended learning environment, students may learn contents outside of the class through websites or Learning Management Systems (LMSs), but engage in practical, hands-on activities during class hours. The author believes the blended learning is a potentially effective approach if implemented for higher education in Aceh, especially Banda Aceh, which has adequate internet access in numerous areas. Integrating the blended learning approach will enhance students’ self-paced learning in Aceh, and in turn improve their critical thinking and collaborative learning. This study also encourages lecturers in Aceh to implement the blended learning approach in their teaching and learning practices, as well as urges the use of various LMSs or Web 2.0 tools as online learning platforms. Finally, the practice of blended learning will support Universities in Aceh in transforming teaching and learning activities from being traditional, to becoming technology-based learning environments.